Human growth hormone promotes engraftment of murine or human T cells in severe combined immunodeficient mice. - Murphy, W J (1992)
Growth hormone (GH) has previously been implicated in T-cell development, and here we test its efficacy in promoting T-lymphocyte engraftment in mice with severe combined immune deficiency (SCID). SCID mice receiving syngeneic thymocytes and treated with recombinant human GH (rhGH) had significantly better T-cell engraftment in their lymph nodes. Human T-cell engraftment was also strongly promoted by rhGH in SCID recipients receiving human peripheral blood lymphocytes. Additionally, although mature human cells have not been thought to enter the murine thymus, human T cells were detected in the SCID thymus after rhGH treatment. Thus, rhGH can be used to optimize long-term peripheral T-cell engraftment in these human-mouse chimeras and may also be useful clinically in treating T-cell deficiencies.